REGULATION OF ACTIVITIES OF GENERAL SECONDARY EDUCATION INSTITUTIONS: FINANCIAL ASPECT - PTASHCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the presented work is to determine the main components of the process of regulating the activities of general secondary education institutions, as well as the main characteristics of the financing process. The main role of the components of the management process in institutions of general secondary education and the components of financial support are determined. The main research methods are: analysis and synthesis - to determine the main components of the process of regulating the activities of general secondary education institutions, methods of deduction and induction - to determine the main aspects of financial support for the activities of general secondary education institutions, graphic method - to visually present the results of the study. Regulation of the activities of general secondary education institutions is an important element of ensuring quality education and sustainable development of the educational system. The state, as the main regulator, establishes the regulatory framework and standards for the functioning of educational institutions, as well as provides funding to ensure the availability and quality of education. The main areas of regulation of general secondary education institutions include: regulatory and legal regulation, financing, quality standards, monitoring and evaluation, personnel development, infrastructure and material and technical support. All these aspects of regulation contribute to the creation of a favorable environment for the development of general secondary education institutions, increasing their efficiency and ensuring the quality of education and upbringing of students. Regulatory policy should be aimed at ensuring the sustainable development of education, taking into account the modern challenges of society and the needs of the labor market. It is important that regulation is flexible and adaptable to changing conditions, providing general secondary education institutions with the opportunity to respond effectively to new challenges and to innovate. Regulation of the activities of institutions of general secondary education includes a number of financial aspects that affect their functioning, development and the quality of the education provided. Financial support is one of the key factors that determines the effectiveness of the educational process and the development of general secondary education institutions. The main aspects of the financial regulation of the activities of general secondary education institutions are defined: state funding. The government allocates budget funds to ensure the functioning and development of general secondary education institutions. State funding ensures the basic level of provision of educational services and infrastructure needs of institutions; regulation of tariffs and prices. The state can regulate the level of tuition fees in institutions of general secondary education to ensure the availability of education for different sections of the population; financial control. Institutions of general secondary education are subject to financial control by state inspection bodies, which allows for effective and economical use of budget funds; investment attraction. General secondary education institutions can attract additional funds from external sources, such as grants, sponsorships, donations, etc. This allows to increase financial resources and implement new projects and programs; financial support of educational programs. The state can provide financial support to individual educational programs and initiatives aimed at improving the quality of education and development of institutions; formation of budgets: General secondary education institutions form their budgets, taking into account needs and profitability, as well as the goals and objectives facing them. The financial aspect of regulating the activities of institutions of general secondary education is important for ensuring the stability of their work, improving the quality of education and ensuring accessibility for all segments of the population.